2018
DOI: 10.1007/s00345-017-2166-6
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater reliability in the radiological classification of renal injuries

Abstract: The finding of substantial IRR amongst radiologists and urologists utilizing the AAST system supports continued use of the broad parameters of the AAST system, with some modification in specific categories with lower agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Additionally, in their study, grading agreements were lower between different specialties compared with readers from the same specialty. Pretorius et al 27 reported slightly higher intradisciplinary and interdisciplinary agreements in grading the renal injuries; however, the agreement for specific AAST grades were still low especially for grade IVand V injuries. These findings demonstrate the interdisciplinary differences in interpretation of the grading system and the need for a more clear and objective grading system that will have higher reproducibility.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, in their study, grading agreements were lower between different specialties compared with readers from the same specialty. Pretorius et al 27 reported slightly higher intradisciplinary and interdisciplinary agreements in grading the renal injuries; however, the agreement for specific AAST grades were still low especially for grade IVand V injuries. These findings demonstrate the interdisciplinary differences in interpretation of the grading system and the need for a more clear and objective grading system that will have higher reproducibility.…”
Section: Discussionmentioning
confidence: 97%
“…An ideal renal injury classification system should be based on well-defined and objective criteria. 25,27 Using clinically relevant radiographic findings that are easy to identify and measure can also help to decrease subjectivity in grading and facilitate reader training. 27 By including some of the important radiographic findings, such as active bleeding and hematoma characteristics in the grading system, the 2018 revisions provide a more clinically relevant classification of renal injuries (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of the AAST classification to include CT-identified injury patterns removes ambiguity in assigning grades and maintains inter-rater reliability. 31 The revision committee acknowledged that the grade of injury, in the presence of vascular trauma, maybe higher than the previously described parenchymal-based injury. Also, the committee recognized that vascular injuries are associated with higher NOM failure rate.…”
Section: Workflowmentioning
confidence: 98%